2022
DOI: 10.3390/molecules27031142
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Immunoregulatory Action of Sesquiterpene Lactones

Abstract: Sesquiterpene lactones (SL), characterized by their high prevalence in the Asteraceae family, are one of the major groups of secondary metabolites found in plants. Researchers from distinct research fields, including pharmacology, medicine, and agriculture, are interested in their biological potential. With new SL discovered in the last years, new biological activities have been tested, different action mechanisms (synergistic and/or antagonistic effects), as well as molecular structure–activity relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 148 publications
0
34
0
Order By: Relevance
“…Little is known about the effects of sesquiterpene lactones on tumor cells, specifically on PDAC and the immunomodulation response, despite allergic reactions of STLs due to activation of immune system has been described [ 131 ]. It seems to have a stimulating role over cytotoxic immune cells, favoring the elimination of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the effects of sesquiterpene lactones on tumor cells, specifically on PDAC and the immunomodulation response, despite allergic reactions of STLs due to activation of immune system has been described [ 131 ]. It seems to have a stimulating role over cytotoxic immune cells, favoring the elimination of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive dietary components play a large role in regulating gut health and resistance to enteric pathogen infections. Our recent work with chicory has identified that SL have a clear anthelmintic activity, and it is known that SL (especially those derived from chicory) are anti-inflammatory and antibacterial compounds [32, 33]. Thus, we examined the effects on parasitic infection and gut microbiota in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical structures of SLs allow for different target interactions, mainly due to the α-methylene-γ-lactone moiety, making SLs able to modulate different cellular responses. At the molecular level, SLs impact different signal pathways, being the NF-kB, MAPK, and JAT-STAT the most well-described ones [ 37 ]. The impact of C. cardunculus leaf extracts on the circadian clock had not been addressed in previous studies.…”
Section: Discussionmentioning
confidence: 99%